3D-printed, configurable, paper-based, and autonomous multi-organ-on-paper platforms. Issue 11 (24th August 2022) - Li, Hongbin; Cheng, Feng; Wang, Zixuan; Li, Wanlu; Robledo-Lara, Juan Antonio; Zhang, Yu Shrike
Abstract : We report 3D-printed, configurable, paper-based organ-on-paper platforms where autonomous and continuous delivery of media to engineered microtissue models is readily achieved without requiring external electrical power during device operations. Abstract : We report the development of a class of 3D-printed, configurable, paper-based organ-on-paper platforms where autonomous and continuous delivery of media to engineered microtissue models is readily achieved without requiring external electrical power during device operations. Here, a passive flow with well-controlled flow rates was initiated along the flow path by capillary and evaporation-driven forces. Cell types representing the vasculature (human umbilical vein endothelial cells), the liver (HepG2 hepatocyte-like cells), the tumor (A549 lung cancer cells), and the kidney (HK-2 kidney proximal tubular cells) were cultured in the different, pre-configured, 3D-printed organ-on-paper platforms. We adopted cisplatin and the prodrug capecitabine as model drugs, which exhibited varying cytotoxicity and metabolism-dependent efficacy outcomes in the various single- or multi-organ models demonstrated. These 3D-printed, configurable, paper-based, cost-effective, and autonomous multi-organ-on-paper platforms would enable convenient generation of shelf-storable organ-mimicking structures, allowing for point-of-care construction of high-content in vitro microphysiological systems to rapidly evaluate both on-target efficacies and/or off-target toxicities, for potential applications in preclinical drug screening and personalized therapeutic selection.